Why Does Spousal Education Matter for Earnings? Assortative Mating and Cross‐Productivity - Huang, Chong; Li, Hongbin; Liu, Pak Wai; Zhang, Junsen (Journal of Labor Economics, 2009)
Spousal education is correlated with earnings for two reasons: cross‐productivity between couples and assortative mating. This article empirically disentangles the two effects by using Chinese twins data. We have two innovations: using twins data to control for the unobserved mating effect in our estimations and estimating both current and wedding‐time earnings equations. We find that both crossproductivity and mating are important in explaining the current earnings. Although the mating effect exists for both husbands and wives, the cross‐productivity effect mainly runs from Chinese husbands to wives. Our findings shed light on the theories of human capital, marriage, and the family.